STRUKTUR ASET DAN EARNING PER SHARE TERHADAP NILAI PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - Lilianti, Emma (Universitas muhammadiyah palembang, 2013)
This research entitled Asset Structure (SA) and Earning per Share (EPS) on firm value in the minning sector listing on Indonesia Stock Excange (BEI). This Study aims to determine the effect of asset structure and Earning per Share (EPS) on firm value in the minning sector listing on Indonesia Stock Excange (BEI). There are two problems in this study are firstly whether asset structure and Earning per Share (EPS) together signifikan effect on firm value on the company sector minning who enrolled in BEI. The second is asset structure and Earning per Share (EPS) have a significant effect partially on minning companies listed on the Indonesia Stock Exchange (BEI). The data used in this research is twenty the minning industry listing at Indonesia Stock Exchange (BEI) from 2007 until 2010, with used multiplelinear regression method and classic asumsion test are normality test, multicoliniarity test, heterocesdasticity and autocorelation Test result linear regression shows the capital structure significant negatif effect, and together the value of the company in listed on BEI. Partially, asset structure have a negative and significant effect on firm value in minning companies listed on the BEI. While Earning per Share (EPS) has no significant effect both together and pastially on the value of the company in the minning sector listing on the BEI.